Role of Orai1 and store‐operated calcium entry in mouse lacrimal gland signalling and function. (6th January 2014) - Xing, Juan; Petranka, John G.; Davis, Felicity M.; Desai, Pooja N.; Putney, James W.; Bird, Gary S.
Abstract : Key points: Lacrimal acinar cells from mice whose gene for Orai1 has been deleted have no detectable store‐operated Ca 2+ entry, whether assessed by measurement of cytoplasmic Ca 2+ changes or as a store‐operated current. Mice lacking Orai1 have diminished lacrimal fluid secretion in response to muscarinic–cholinergic stimulation. Mice lacking Orai1 also show diminished exocytosis, both in vivo and in vitro . The development and morphology of lacrimal glands, as well as responses not dependent on Ca 2+ entry were unchanged in the knockout mice. The results demonstrate the central importance of store‐operated Ca 2+ entry in lacrimal exocrine function, and suggest possible strategies for combating diseases associated with diminished lacrimal secretion. Abstract: Lacrimal glands function to produce an aqueous layer, or tear film, that helps to nourish and protect the ocular surface. Lacrimal glands secrete proteins, electrolytes and water, and loss of gland function can result in tear film disorders such as dry eye syndrome, a widely encountered and debilitating disease in ageing populations. To combat these disorders, understanding the underlying molecular signalling processes that control lacrimal gland function will give insight into corrective therapeutic approaches. Previously, in single lacrimal cells isolated from lacrimal glands, we demonstrated that muscarinic receptor activation stimulates a phospholipase C‐coupled signalling cascade involving the inositol trisphosphate‐dependent mobilization of intracellular calcium and the subsequent activation of store‐operated calcium entry (SOCE). Since intracellular calcium stores are finite and readily exhausted, the SOCE pathway is a critical process for sustaining and maintaining receptor‐activated signalling. Recent studies have identified the Orai family proteins as critical components of the SOCE channel activity in a wide variety of cell types. In this study we characterize the role of Orai1 in the function of lacrimal glands using a mouse model in which the gene for the calcium entry channel protein, Orai1, has been deleted. Our data demonstrate that lacrimal acinar cells lacking Orai1 do not exhibit SOCE following activation of the muscarinic receptor. In comparison with wild‐type and heterozygous littermates, Orai1 knockout mice showed a significant reduction in the stimulated tear production following injection of pilocarpine, a muscarinic receptor agonist. In addition, calcium‐dependent, but not calcium‐independent exocytotic secretion of peroxidase was eliminated in glands from knockout mice. These studies indicate a critical role for Orai1‐mediated SOCE in lacrimal gland signalling and function.